Analisis kemampuan pemodelan matematika melalui konteks produksi pempek ditinjau dari self-efficacy - Suryati Suryati; Dwi Astuti; Akhmad Fajari; Uzair Uzair; Nila Kesumawati; Allen Marga Retta (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2026)
Research on ethnomathematics has generally emphasized the use of cultural contexts. The present study aims to analyze students’ mathematical modeling ability based on self-efficacy levels through the ethnomathematics context of pempek production. This study employs a mixed-methods approach with a sequential explanatory design involving 36 tenth-grade students of SMKN 1 Buay Madang. Data were collected through self-efficacy questionnaires, mathematical modeling tests, and semi-structured interviews, and were analyzed using descriptive quantitative analysis and Miles & Huberman’s qualitative model, then integrated at the interpretation stage. The findings indicate a tendency for differences in mathematical modeling ability based on self-efficacy levels, where students with higher self-efficacy tend to demonstrate more complete modeling processes. Furthermore, the pempek production context in this study is understood as a contextual situation that helps students connect mathematical problems with real-life situations, rather than as an evaluation of the effectiveness of an instructional intervention. These findings highlight the importance of integrating self-efficacy and ethnomathematical contexts in vocational mathematics education.